2022
DOI: 10.33059/jseb.v13i1.3982
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jumlah Angkatan Kerja dan Investasi terhadap Pendapatan Asli Daerah

Abstract: The purpose of this study is to analyze the effect of the number of labor force and investment on Regional Original Income Revenue (PAD). Provincial PAD in Indonesia has different figures for each province. Every year the PAD figure fluctuates and forms a certain pattern for each province. The number of labor force and investment is estimated to affect the amount of PAD figure. The research used data from 34 provinces in Indonesia taken from the Central Statistics Agency in 2020, and analyzed using the multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…According to [4] in their study revealed that the number of workers will have a positive impact on PAD. This is evidenced by the results of research conducted by [5] which in the results of his research revealed that the Number of Labor Force has an influence on Regional Original Income.…”
Section: Workforcementioning
confidence: 92%
“…According to [4] in their study revealed that the number of workers will have a positive impact on PAD. This is evidenced by the results of research conducted by [5] which in the results of his research revealed that the Number of Labor Force has an influence on Regional Original Income.…”
Section: Workforcementioning
confidence: 92%
“…Untuk itu, Provinsi Aceh harus terus berbenah untuk dapat menciptakan kesejahteraan dengan meningkatkan faktor-faktor yang mempengaruhi pertumbuhan perekonomian tersebut secara makro. Diantara faktor-faktor yang dimaksud adalah peningkatan nilai investasi, jumlah tenaga kerja dan Pendapatan Asli Daerah (Eliza, 2015;Hartanti, 2017;Ifrizal et al, 2014;Isma, 2014;Lisa & Priyagus, 2017;Maharani, 2016;Mahriza & Amar B, 2019;Manduapessy, 2020;Nisa, 2017;Norlita, 2018;Nuryasman, 2012;Rizal, 2020;Tianto, 2022). Sebagaimana terlihat pada gambar berikut: Gambar 2.…”
Section: Pendahuluanunclassified
“…Sementara itu dalam beberapa penelitian disebutkan bahwa PAD dalam perkembangannya juga dipengaruhi oleh besarnya jumlah investasi dan jumlah tenaga kerja (Hartanti, 2017;Ifrizal et al, 2014;Tianto, 2022). Hal ini kemudian mendasari lahirnya hipotesis dalam penelitian ini yakni: b. Jika nilai t hitung < t tabel maka indirect efect tidak signifikan.…”
Section: Pendapatan Asli Daerah (Pad)unclassified